16-3*-2=x

Simple and best practice solution for 16-3*-2=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16-3*-2=x equation:


Simplifying
16 + -3 * -2 = x

Multiply -3 * -2
16 + 6 = x

Combine like terms: 16 + 6 = 22
22 = x

Solving
22 = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
22 + -1x = x + -1x

Combine like terms: x + -1x = 0
22 + -1x = 0

Add '-22' to each side of the equation.
22 + -22 + -1x = 0 + -22

Combine like terms: 22 + -22 = 0
0 + -1x = 0 + -22
-1x = 0 + -22

Combine like terms: 0 + -22 = -22
-1x = -22

Divide each side by '-1'.
x = 22

Simplifying
x = 22

See similar equations:

| 28+(+63)= | | 12x-5x-10y+y= | | .20(45-x)=x^2 | | -7x+8=13 | | x-4.5=2.5 | | -5(-2-3z)-8v=25 | | 23+(+20)= | | 12k+14=10k-2k-14 | | 5/6x-3+1/3x=7/24x+1/8 | | s=25+0.75 | | -9=-4+x/17 | | n+(-4)+(-6n)+(-10)= | | 3a+11=-4 | | -4p-2p+8p-15+3= | | 9(d+2)=3(d-2) | | -6(-x-7)=90 | | 1128/(-47)= | | 3x+5x=2(4+7) | | -2x-4(0.25+0.5x)=1 | | 15p+7q+5p-4q= | | (1-7i)-(1-5i)= | | 5t-3=7 | | X/18+1=-3 | | (a^8b^2)(a^6b^8)= | | 4x-6x=x-9 | | b=85+(10+7)w | | 10x/5x-1=5+2/5x-1 | | 7x-(-4)=54 | | 7(r-1)-3=2r+5 | | -7(n+7)=4n-16 | | 4x+9-x= | | ln(4-2x)+ln(9-3x)=21n(x+1) |

Equations solver categories